SPIRITUAL APPROACH TO REDUCE ANXIETY IN PREGNANT MOTHER WITH LONG-STANDING BABY IN WANDANPURO VILLAGE: A CASE STUDY - Suhaelah, Suhaelah; Hidayah, Ridhoyanti (Universitas Nahdlatul Ulama Surabaya, 2022)
Background: Pregnancy is a phase that causes many changes in a woman's life, from physical, psychological, hormonal, and social changes. Anxiety is a psychological manifestation that is commonly found in pregnant women. Pregnant women's anxiety because the baby lies transversely will increase the risk of umbilical cord prolapse during labor. Objective: The purpose of this study was to determine the spiritual approach to reduce anxiety in pregnant mother with long-standing baby in Wandanpuro village. Methods: The writing methodology uses the analytical method of nursing care with a descriptive design. The participants were pregnant women with anxiety due to the transverse position of the baby. History of previous deliveries: The client has usually given birth, with the baby being breech in the first delivery and coiling the umbilical cord in the second. The lack of socializing with the surrounding environment and husband involvement significantly causes anxiety, stress, and depression in pregnant women. The anxiety problem, in this case, was then followed up with nursing interventions according to the nurse's competence, namely an anxiety implementation strategy (SP) for clients and families in the form of spiritual activities. Result: The most preferred therapy and considered most effective by clients for overcoming the anxiety of spiritual activities are regular worship, namely praying five times a day and routine dhikr after every prayer. The factor of faith has a broad and robust influence on health. Conclusion: Spiritual support will form an adaptive coping mechanism for an event threatening the client's survival.